Comparison Socio-Psychological Characteristics of Professional Development of Students of Different Specialties (Spiritual and Secular Universities) - Kostruba, Natalia (Psychological Prospects Journal, 2018)
The article is devoted to the study the socio-psychological differences in professional formation of students of different specialties in spiritual and secular universities (psychologists, religious scholars, theologians). The analysis of such differences were considered within the stages of professional formation (adaptation, mastery and implementation). To achieve the purpose of the study, a complex of 15 psychodiagnostic techniques was used. The obtained results allow to state that there are statistically significant differences between groups (p